2016
DOI: 10.1108/tc-12-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of clients’ experiences of group therapy

Abstract: Purpose – Much previous research has explored the impact of group work on the therapist. The purpose of this paper is to examine how group members tolerate the powerful material discussed in groups in a prison-based therapeutic community. The authors briefly describe the regime at HMP Grendon and previous research into the impact of group work on therapists. Design/methodology/approach – A qualitative approach using a focus group was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…These included encouraging people to speak generally about sensitive topics in focus groups without personal disclosure (Hatton et al, 2006; Pritchard, Jordan, & Jones, 2014; Staton-Tindall et al, 2007) and designing study advertisements to allow people to attend groups because of general views on a topic rather than personal experience (Pritchard et al, 2014). Some researchers discussed the need to carefully ensure participant understanding of focus group methods and the limits on privacy and confidentiality in the prison context (Akerman & Geraghty, 2016; Kuo et al, 2014). A useful strategy was to hold meetings ahead of the focus groups to discuss their scope and process so participants were more comfortable and were less likely to disclose any sensitive personal matters during the actual focus groups (Akerman & Geraghty, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included encouraging people to speak generally about sensitive topics in focus groups without personal disclosure (Hatton et al, 2006; Pritchard, Jordan, & Jones, 2014; Staton-Tindall et al, 2007) and designing study advertisements to allow people to attend groups because of general views on a topic rather than personal experience (Pritchard et al, 2014). Some researchers discussed the need to carefully ensure participant understanding of focus group methods and the limits on privacy and confidentiality in the prison context (Akerman & Geraghty, 2016; Kuo et al, 2014). A useful strategy was to hold meetings ahead of the focus groups to discuss their scope and process so participants were more comfortable and were less likely to disclose any sensitive personal matters during the actual focus groups (Akerman & Geraghty, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers discussed the need to carefully ensure participant understanding of focus group methods and the limits on privacy and confidentiality in the prison context (Akerman & Geraghty, 2016; Kuo et al, 2014). A useful strategy was to hold meetings ahead of the focus groups to discuss their scope and process so participants were more comfortable and were less likely to disclose any sensitive personal matters during the actual focus groups (Akerman & Geraghty, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Managing integration of men who have committed sexual offences into a TC is not without its challenges; emotions are raised in residents and staff when hearing the details of offences, and hierarchies can still be in place and need to be recognised and explored (see Akerman & Geraghty, 2016). Just as in the community outside of custody, inside prisons, there can be negative attitudes toward those who commit sexual offences.…”
Section: Applying To and Engaging In A Tcmentioning
confidence: 99%
“…Many applicants identify problems from their childhood that they want to understand and manage and, through doing so, negate the powerful and destructive repressed emotions. They report having experienced adverse childhood experiences (e.g., at the time of Akerman & Geraghty's research 50% report having had acts of self-harm, 52% having experienced physical abuse, 32% having a history of sexual abuse, and 69% report having had a significant separation from their primary caregiver), and as Akerman and Geraghty (2016) explained, this has impacted on their interpersonal relationships and behaviour. As is often the case with those who have had adverse experiences, their response to reactivated trauma can be aggressive, and so maintaining a trauma-informed approach is vital (see Jones, 2018).…”
Section: Applying To and Engaging In A Tcmentioning
confidence: 99%
“…They note similarities to how other youths have managed their emotions, while also recognising differences too. Those involved in the programme, albeit a small sample, indicated that they thought there was a need to be more creative in the approach to tackling gang crime and the importance of adopting a holistic approach which can address both psychological and societal issues (Akerman and Geraghty, 2016;Geraghty and Akerman, 2017).…”
Section: Changing the Game Programmementioning
confidence: 99%